Overcoming Anxiety in Hemodialysis Patients with Mindfulness Therapy: Literature Review - Yuwono, Trisno; Wardani, Ratna; Prasetyo, Joko (Journal of Applied Nursing and Health, 2024)
Background: Individuals suffering from chronic kidney failure who undergo Hemodialysis therapy are prone to experiencing anxiety. The literature review aims to determine the importance of Mindfulness in overcoming anxiety in chronic kidney failure patients undergoing hemodialysis therapy. Methods: The design uses the PRISMA approach. The whole text and the year of publication are considered when making selections during the research stage. Additionally, journals and papers that were judged less important were not included. Seven pertinent papers were found through Google Scholar, Indonesia One Search, DOAJ, and Garuda using the keywords "mindfulness therapy," "hemodialysis," and "anxiety." Results: After reviewing the selected articles, it was found that by administering mindfulness therapy, the anxiety level of chronic kidney failure patients undergoing hemodialysis therapy decreased Conclusion: Mindfulness therapy can be used to decrease the anxiety level of chronic kidney failure patients undergoing hemodialysis.